DIGITAL MARKETING INFORMATION SYSTEMS FOR RECOMMENDATION PROMOTION PRODUCT USING APRIORI ALGORITHM - Risman Nurdiansyah; Anggraeni Pratiwi; Tresyia Nidia Syukri; Yasir Basyara Hilmi; Ari Purno Wahyu (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The information technology currently influences the world of trade and sale and purchase transactions, in the beginning a transaction requires a meeting place between sellers and buyers, the media is currently ineffective because it causes sales not optimal because of limited space and promotional media, the use of information media in the form of e-commerce media is able to provide choices of types of goods with different categories of goods, e-commerce information systems can be used to classify the types of products or goods most sold and able to as references and giving discounts to customers, each database of goods sales will be analyzed using Apriori algorithm and FP-Growth, from the data the system will automatically provide information about the most sold items that will be used as product recommendations to be given to customers.